Identification and optimisation of a series of tetrahydrobenzotriazoles as metabotropic glutamate receptor 5-selective positive allosteric modulators that improve performance in a preclinical model of cognition. Issue 24 (15th December 2015) - Ellard, John M.; Madin, Andrew; Philps, Oliver; Hopkin, Mark; Henderson, Scott; Birch, Louise; O'Connor, Desmond; Arai, Tohru; Takase, Kazuma; Morgan, Louise; Reynolds, David; Talma, Sonia; et al.
Graphical abstract: Abstract: Herein we describe a series of tetrahydrobenzotriazoles as novel, potent metabotropic glutamate receptor subtype 5 (mGlu5) positive allosteric modulators (PAMs). Exploration of the SAR surrounding the tetrahydrobenzotriazole core ultimately led to the identification of29 as a potent mGlu5 PAM with a low maximal glutamate potency fold shift, acceptable in vitro DMPK parameters and in vivo PK profile and efficacy in the rat novel object recognition (NOR) assay. As a result29 was identified as a suitable compound for progression to in vivo safety evaluation.